Pharmaco-imaging in drug and biologics development : fundamentals and applications - Cheruvu, Narayan P.S; Hu, Tom C.-C; Moyer, Brian R. (AAPS Advances in the Pharmaceutical Sciences Series, 2014)
Advances in drugs and biologics to mitigate or cure some of nature's most complex medical problems have been incredible to behold.  These accomplishments are due to the actions of a wide theatre of participants from biologists, pharmacologists, geneticists, chemists and manufacturers, molecular biologists, toxicologists, clinicians, nurses, program managers, quality assurance personnel, regulatory professionals and - a new group of innovators - the Imaging Scientists.  Imaging has grown from the microscopy sections put on slides with special stains to now in vivo "slices" created with innovative physics, imaging tracers and contrast agents, and incredibly fast and accurate computational systems.  The world of biology has become one of witnessing the actions of drugs and biologics through the window of mechanical and electrical engineering - creating  instruments and reporter molecules that can help us "see" into our bodies and "paint" them with medical information needed to resolve disease. This book will inspire imagination and elicit even more innovations in the development of new and novel drugs and biologics through imaging.